How do specialist trainee doctors acquire skills to practice patient-centred care? A qualitative exploration. Issue 10 (15th October 2018) - Patel, Veena; Buchanan, Heather; Hui, Michelle; Patel, Prashanth; Gupta, Pankaj; Kinder, Alison; Thomas, Hywel
Abstract : Objectives: The importance of patient-centred care (PCC) has been increasingly recognised. However, there is limited work exploring what doctors actually understand by PCC, and how they perceive they acquire PCC skills in the workplace. The objectives of our study were to explore (1) what UK doctors, in specialist training, perceive to be the essential components of PCC, (2) if/how they acquire these skills, (3) any facilitators/barriers for engaging in PCC and (4) views on their PCC training. Design: Qualitative study using in-depth individual semi-structured interviews with UK specialist trainees. Interview transcripts were thematically analysed. Setting and participants: Thirty-one specialist trainee doctors, with at least 4 years postgraduate experience, were interviewed. Participants worked in various medical specialities within the Medical Directorate of an acute hospital in the East Midlands of England. Results: Interview data were transcribed verbatim and categorised into three main themes. The first theme was 'Understanding PCC' where the doctors gave varied perspectives on what they understood by PCC. Although many were able to highlight key components of PCC, there were also some accounts which demonstrated a lack of understanding. The second theme was 'Learning PCC skills: A work in progress'. Learning to be patient-centred was perceived to be an ongoing process. Within this, trainee doctors reported 'on-the-job' learning as the main means of acquiring PCC skills, but they also saw a place for formal training (eg, educational sessions focussing on PCC, role play). 'Delivering PCC: Beyond the physician' referred to the many influences the doctors reported in learning and delivering PCC including patients, the organisation and colleagues. Observing consultants taking a patient-centred approach was cited as an important learning tool. Conclusions: Our findings may assist clinical educators in understanding how trainee doctors perceive PCC, and the factors that influence their learning, thereby helping them shape PCC skills training.